2021
DOI: 10.1055/s-0040-1721125
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of the Distal Femur Width to the Tibial Plateau Width with Advancing Age

Abstract: Historically, intraoperative analysis of knee fracture procedures relied upon a fluoroscopic reduction assessment by the surgeon. This is a subjective assessment due to the lack of linear measurement reference data. Compared with the knee, the ankle and wrist have well-established bony anatomical relationships to guide reduction assessment during fracture treatment. The purpose of this study was to (1) determine the width ratios in the knee (plateau to femur) with aging, and (2) determine knee width changes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A recent study by Schlatterer et al found that both femoral and tibial articular width was increased by 8 and 9.3 mm respectively in patients aged 61–80 [ 11 ]. While our study lacked the power to detect differences between age groups, this tendency towards a wider articular surface in the elderly cohort should be considered when performing reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Schlatterer et al found that both femoral and tibial articular width was increased by 8 and 9.3 mm respectively in patients aged 61–80 [ 11 ]. While our study lacked the power to detect differences between age groups, this tendency towards a wider articular surface in the elderly cohort should be considered when performing reduction.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). The contralateral, uninjured limb can be used as a viable template for assessing patient specific condylar width metrics [ 9 11 ]. Pathologic widening of the injured tibial plateau, and therefore assessment of adequate reduction, is determined by comparison to the uninjured, native anatomy.…”
Section: Introductionmentioning
confidence: 99%